HUBUNGAN MEKANISME KOPING DENGAN REGULASI EMOSI PADA REMAJA PUTRI YANG MENGALAMI DISMINORE - Ferdinda Ajeng Selyani; Dhian Ririn Lestari; Kurnia Rachmawati (CNJ: Caring Nursing Journal, 2022)
Dysmenorrhea is a feeling of pain in lower abdomen at the time of menstruation. Someone become more very emotional when dysmenorrhea due to excessive estrogen production. Coping mechanism is needed as the ability to organize emotions and to get through in any changing of sitations. Humans also have emotion control. The emotions control calls emotional regulation, its function for controlling the emotions to keep have a good interaction with other people around them. The objective was to know the correlation of coping mechanism with emotional regulation on teenage girls who had dysmenorrhea in SMP Negeri 2 Banjarbaru. This research used cross sectional design. The samples were 134 respondents collected by stratified random sampling. The reseach instrument was questionnaire sheet. Data analysis used spearman correlation statistic test with 95% confidence level (α=0.05). There was a positive correlation between coping mechanism with emotional regulation in teenage girls who has dysmenorrhea. This correlation was very weak (p value 0,004 and r=0,247). The mechanism of coping on their dysmenorrhea period will be affected to the emotional regulation. The worse the coping mechanism used is the lower the emotional regulation will show up.